Synthesis and antitumor activity of litseaone B analogues as tubulin polymerisation inhibitors. (31st December 2022) - Yang, Wei; Peng, Huining; Huang, Yong; Peng, Zhiyun; Wang, Guangcheng
Abstract: A series of litseaone B analogues 4a∼4p were synthesised and antitumor activities of all compounds were screened. These compounds were designed by introducing different substituents on the B ring. Among these synthesised compounds, it was proved that 4k showed excellent activity against A549, HepG2, and HCT-15 cell lines, the IC50 values were 7.60 μM, 20.53 μM, and 4.59 μM, respectively. The results of tubulin polymerisation inhibition and immunofluorescence staining experiments displayed that 4k could act on tubulin and inhibit the polymerisation of tubulin. Moreover, the wound healing assay showed that 4k could inhibit the migration of A549 cells in a dose-dependent manner. Furthermore, the results of flow cytometry revealed that 4k was capable of blocking the cell cycle in the G2/M phase, inducing a decrease in the mitochondrial membrane potential and ultimately leading to apoptosis in A549 cells. Importantly, the possible binding model was also performed by molecular docking. Subject classification codes: short communication. Graphical Abstract: UF0001